Links between postural stability and neurodynamic characteristics in kickboxers - Korobeynikov, G.; Bulatova, M.; Zhirnov, O.; Cynarski, W. C.; Wasik, J.; Korobeinikova, L.; Volskiy, D.; Mishchenko, V.; Malinskiy, I.; Sergienko, U. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Purpose - study of links between neurodynamic functions and postural stability in elite kickboxers. Methods. 27 kickboxers, aged 12-15 were examined. The apparatus-programs complex «Psychotest-NS» was used for the study of neurodynamic functions. The study of postural stability was conducted using the plural stabilograms «Stabilan» method. Results. The results show that kickboxers with a higher level of postural stability have a lower square of oscillation of the total center of mass of the body during visual deprivation. This higher level of postural stability in kickboxers is linked to increasing accuracy and attention in conditions of differential informational processing, with a simultaneous decline in muscular force and lowering of speed of sensory-movement response to complex stimulus. Kickboxers with lower levels of postural stability revealed more high meanings of muscular force and speed of sensory-movement response to differential visual stimuli.Conclusions. The study has revealed the functional links between postural stability and neurodynamic characteristics in kickboxers. Received data can be used in the training process of qualified kickboxers to improve training activity and give higher sport results.